2016
DOI: 10.1093/humrep/dew308
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the human sperm DNA methylome to folic acid fortification and short-term supplementation

Abstract: STUDY QUESTION: Do short-term and long-term exposures to low-dose folic acid supplementation alter DNA methylation in sperm?SUMMARY ANSWER: No alterations in sperm DNA methylation patterns were found following the administration of low-dose folic acid supplements of 400 μg/day for 90 days (short-term exposure) or when pre-fortification of food with folic acid and post-fortification sperm samples (long-term exposure) were compared.WHAT IS KNOWN ALREADY: Excess dietary folate may be detrimental to health and DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…Researchers have showed anomalies in sperm DNA methylation and homocysteine accumulation in men with infertility. As regards to high level folate and B12 in traditional and healthy dietary pattern and above mechanisms, this diet can prevent DNA damage and also improved sperm concentration and motility (32,37).studies showed increase oxidative stress level can effect on sperm motility and increase DNA fragmentation, also based on this finding, intake of antioxidants increases sperm concentration and improves its progressive motility (21,35).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Researchers have showed anomalies in sperm DNA methylation and homocysteine accumulation in men with infertility. As regards to high level folate and B12 in traditional and healthy dietary pattern and above mechanisms, this diet can prevent DNA damage and also improved sperm concentration and motility (32,37).studies showed increase oxidative stress level can effect on sperm motility and increase DNA fragmentation, also based on this finding, intake of antioxidants increases sperm concentration and improves its progressive motility (21,35).…”
Section: Discussionmentioning
confidence: 95%
“…Folate and B12 are critical nutrients for methylation, stability and DNA replication. DNA methylation is a biochemical process that is involved in normal development and cellular differentiation (35). Much research has demonstrated that abnormal DNA methylation and acetylation associated with chronic and congenital diseases (36).…”
Section: Discussionmentioning
confidence: 99%
“…[ 5–7,12,14–22 ] A total of five studies investigated the association between folate status and sperm epigenetics, of which two were animal studies [ 10,13 ] and three were human studies. [ 5,12,23 ] Six studies investigated the associations between folate status and sperm DNA damage and apoptosis, including two animal studies [ 11,13 ] and four human studies ( Table 2 ). [ 7,19,21,24 ]…”
Section: Resultsmentioning
confidence: 99%
“…A total of three studies investigated the effect of folate status on sperm DNA methylation. [ 5,12,23 ] The recent study of Chan et al. showed that multiple years of FA food fortification in Canada had no significant influence on sperm overall DNA methylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation